L’ÉCRITURE COMME FORME D’IDENTITE CULTURELLE DANS LA LITTÉRATURE FRANCOPHONE À TRAVERS LE BAC DE CABRI MORT DE MAHAMADOU KONATÉ - ISSIAKA, Diafar; BAYOKO, Yaya; Coulibaly, Youssouf; ZOROME, Soungalo (International Journal of Scientific Research and Management (IJSRM), 2024)
Cultural identity is linked to language. Malian literature, like all literature, has an identity. This cultural identity presents its particularity in that it makes it possible to identify in certain cases the ethnicity of the author through the use of his mother tongue in his writings. Thus in the short story entitled Le Bac de Cabri mort by Mamadou Konaté that we have chosen to study there are words and expressions from the author's mother tongue or one of the national languages ​​of Mali. Which clearly shows that the mother tongue faces the French language which was the official language in Mali before becoming a working language. We tried to understand the author's choice in this short story regarding the use of terms and expressions relating to the Bambara language.